2020
DOI: 10.4102/phcfm.v12i1.2222
|View full text |Cite
|
Sign up to set email alerts
|

The outpatient management of hypertension at two Sierra Leonean health centres: A mixed-method investigation of follow-up compliance and patient-reported barriers to care

Abstract: Background Sub-Saharan Africa faces an increasing burden of non-communicable diseases. In particular, hypertension and its therapeutic control present a challenge and opportunity for health practitioners and health systems within the region. Aim This study sought to assess an initiative conducted by two health clinics to begin treatment of hypertension amongst their patient populations by reviewing medication possession rates and documenting patient-reported barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…A home visit on top of routine care delivered at clinic consultation rooms is more likely to reach patients who are busy during office hour or those with disabilities, and thus physicians are more prone to achieve the recommended goal of follow-up frequency. This echoes existing literature on patient-reported barriers to routine follow-up care for hypertension and diabetes in low-income settings, including but not limited to transportation, financial burden and schedule conflicts, along with treatment adherence and satisfaction [ 45 , 46 ]. Besides, it has been suggested that therapeutic-related factors could also be related with achieving optimal practices in disease management on top of health education [ 16 , 17 , 34 ].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A home visit on top of routine care delivered at clinic consultation rooms is more likely to reach patients who are busy during office hour or those with disabilities, and thus physicians are more prone to achieve the recommended goal of follow-up frequency. This echoes existing literature on patient-reported barriers to routine follow-up care for hypertension and diabetes in low-income settings, including but not limited to transportation, financial burden and schedule conflicts, along with treatment adherence and satisfaction [ 45 , 46 ]. Besides, it has been suggested that therapeutic-related factors could also be related with achieving optimal practices in disease management on top of health education [ 16 , 17 , 34 ].…”
Section: Discussionsupporting
confidence: 66%
“…Thirdly, confounders potentially associated with care delivery such as job satisfaction may not be fully adjusted for in this study, and a physician self-report survey will inevitably restrict inclusion of questions relating to individual characteristics at patient-level. Accordingly, we were unable to differentiate whether patients aren’t coming back out of their own volition versus because of the provider, despite the possibility that patient-level barriers such as transportation, financial burden and schedule conflicts might play a role [ 45 , 46 ]. Fourthly, factors associated with target non-attainment in this study may not directly indicate its correlation with patient outcomes, and the use of a specific health-status measurement as the primary outcome from the patient’s perspective is warranted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the costs for a visit to one of the health facilities was about 40,000 Leones (US$4.75) and costs for antihypertensive medication for a month 50,000 Leones (US$6.00). According to recent 2021 estimates from UNDP 60% of Sierra Leoneans live on less than US$1.25 a day, illustrating how very few people can afford treatment for their hypertension [ 37 , 38 , 39 ]. The shortage of medicines in public facilities drives patients to purchase from private pharmacies or informal sources associated more often with poor quality medicines, which may also result in ineffective treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed an affirmation of all the qualitative appraisal questions. Another study [29] was assessed under the mixed methods section and was also affirmative to all the questions.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The studies were conducted in various countries, including Tanzania [27], Ethiopia [32,33,34,35,36], Ghana [37], Sierra Leone [29], Cameroon [38], Eritrea [28], South Africa [26,39], and Kenya [40]. The various studies used diverse study designs.…”
Section: Study Characteristicsmentioning
confidence: 99%